2000
DOI: 10.1016/s0735-2689(01)80008-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Early Phases of Plant Gravitropism

Abstract: Gravitropism is directed growth of a plant or plant organ in response to gravity and can be divided into the following temporal sequence: perception, transduction, and response. This article is a review of the research on the early events of gravitropism (i.e., phenomena associated with the perception and transduction phases). The two major hypotheses for graviperception are the protoplast-pressure and starch-statolith models. While most researchers support the concept of statoliths, there are suggestions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
129
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(130 citation statements)
references
References 0 publications
1
129
0
Order By: Relevance
“…thaliana roots display phototropism as well as gravitropism and hydrotropism (4)(5)(6). The roots display a negative phototropism in response to unilateral illumination of white or blue light.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…thaliana roots display phototropism as well as gravitropism and hydrotropism (4)(5)(6). The roots display a negative phototropism in response to unilateral illumination of white or blue light.…”
Section: Resultsmentioning
confidence: 99%
“…Roots control their growth orientation by displaying tropisms in response to environmental cues such as gravity, light, physical contact, and moisture gradients (1)(2)(3)(4)(5)(6)(7). These responses are important features for the survival of sessile terrestrial plants in stressful environments such as drought conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The graviresponse also participates in the regulation of apical dominance (5). Intense studies of these forms of gravimorphogenesis led to many discoveries of the molecular mechanisms of gravitropism (6,7). However, the mechanisms for other types of gravimorphogenesis remain unclear, despite their importance.…”
mentioning
confidence: 99%
“…These authors also suggested that the earlyperception phase of hydrotropism occurs in the root cap, because roots grow normally but do not respond to moisture gradients after removal of the cap. Later, Takahashi et al (13) used a starchless mutant of Arabidopsis, which has a greatly reduced sensitivity to gravity compared with WT (14,15), to show it is enhanced in root hydrotropism.…”
mentioning
confidence: 99%